Correlation of elastic modulus and x-ray bone density in the area of the ankle joint - Omelchenko, Taras; Buryanov, Oleksandr; Lyabakh, Andrey; Mazevich, Vadim; Shidlovsky, Mykola; Musienko, Olga (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Objective: to determine the relationship between the X-ray density and the modulus of elasticity of the bone in the ankle joint, using an empirical method (in a natural experimental study). Methods: the modulus of elasticity of 10 samples of the tibia cortical bone and 42 — cancellous bone of the distal part of the tibia, fibula and talus was determined. The study of the bone modulus of elasticity was carried out by recording of linear displacements at static and quasistatic compression loads. X-ray density in Hounsfield units (HU) was estimated using computer tomography. Results: it was found that the average radiological density for cancellous tibia bone tissue was 314.8 HU, and the modulus of elasticity was 581.5 MPa. For the fibula the average values of the corresponding indicators were 258.9 HU and 374.7 MPa; for the talus — 255.6 HU and 445.3 MPa, respectively. For the cortical tibia shaft, the mean value of the X- ray density was 1 887.7 HU, the modulus of elasticity was 10 002.8 MPa. As a result of the regression analysis, a correlation between the radiological density of the bone and its modulus of elasticity in the ankle joint was established. The revealed dependence for cortical bone is described by the formula E = 6,3 ∙ HU – 1905; and for cancellous — E = 3 ∙ HU – 407. Conclusions: the use of the obtained formulas allows noninvasive determination of the modulus of elasticity of bone tissue in patients on the basis of the radiographic density in a standard computer tomography scan with sufficient accuracy.